Dimensi Post-Tradisionalisme Islam dalam Madrasah: Konvergensi Turāth Islam dan Modernitas Barat - Ishom Fuadi Fikri (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
The contemporary Islamic thought was preoccupied with the conflict between the tradition (al-turāth) and the modernity (al-hadāthah). In the midst of this polemic, there is a stream of Islamic Post-Traditionalism in post-reformation Indonesia that offers a cultural transformation without leaving behind the culture itself. This article aims to describe the format of Islamic Post-Traditionalism in the the school culture of Madrasah Aliyah Unggulan Darul ‘Ulum STEP-2 Kemenag RI-IDB Jombang and its implications for the madrasa curriculum formulation. The research method uses a qualitative-phenomenological approach by collecting data through semi-structured interviews, participatory observations, and documentations. The results of this study shows that there are elements of the authenticity (al-aṣālah) and the present (al-mu’āṣirah) in the madrasah culture indicating the continuity of tradition within transformation. This has implications for the formulation of the madrasa curriculum that based on the principle of the conservation and the hybridization, so students can follow the development in the modern world without leaving behind their own traditions.